Effect of Serum and Oxygen Concentration on Gene Expression and Secretion of Paracrine Factors by Mesenchymal Stem Cells - Patrick Page; Joshua DeJong; Alaina Bandstra; Robert A. Boomsma (International Journal of Cell Biology)
Mesenchymal stem cells (MSC) secrete paracrine factors that may exert a protective effect on the heart after coronary artery occlusion. This study was done to determine the effect of hypoxia and serum levels on the mRNA expression and secretion of paracrine factors. Mouse bone marrow MSC were cultured with 5% or 20% serum and in either normoxic (21% O2) or hypoxic (1% O2) conditions. Expression of mRNA for vascular endothelial growth factor (VEGF), monocyte chemotactic protein-1 (MCP-1), macrophage inflammatory protein-1α (MIP-1α), MIP-1β, and matrix metalloproteinase-2 (MMP-2) was determined by RT-qPCR. Secretion into the culture media was determined by ELISA. Hypoxia caused a reduction in gene expression for MCP-1 and an increase for VEGF (5% serum), MIP-1α, MIP-1β, and MMP-2. Serum reduction lowered gene expression for VEGF (normoxia), MCP-1 (hypoxia), MIP-1α (hypoxia), MIP-1β (hypoxia), and MMP-2 (hypoxia) and increased gene expression for MMP-2 (normoxia). The level of secretion of these factors into the media generally paralleled gene expression with some exceptions. These data demonstrate that serum and oxygen levels have a significant effect on the gene expression and secretion of paracrine factors by MSC which will affect how MSC interact in vivo during myocardial ischemia.